Daya Saing Tanaman Kedelai Hasil Desikasi Herbisisda Paraquat dan Glifosat Terhadap Cekaman Gulma - Johan Riry (Jurnal Agrista, 2006)
The Competitive of Soybean Used as Dessicant with Paraquat and Glifosat Herbicide on Stress of WeedsABSTRACT. Herbicide might be use for desicant to increase soybean seed quality at rainy season, however not all herbicide can be used as dessicant. Seed with a better quality will growth faster than weed will, they will form leafy coronet that shaded the weed and be able to compete against to the weed. The experiment was conducted during rainy season at PT Syngeta-Cikampek, West Java, started from November 2003 to March 2004. This experiment that was the second experiment was arranged in two-factor randomized block design with two replications. The first factor was the 21 seeds generated from dessicacy test in experiment 1; the second factor was the invasion status of weed that consist of weed invated and weed free. The observed responses includes the weed’s characteristics that consist of dominant value ratio and the soybean’s response that consist of the height of the plant, the length of the root, the weight of 100 seed. The data was analyzed by Percentage Change Test, Least Significant Increase (LSI) Test, Stres Tolerant Index (STI) Test and continued by Directed STI, The result shows that the seed generated from paraquat herbicide dessicacy at dose of 0.4 kg a.a ha-1 applicated at R2 are more superior than other seed treated by any oyher treatment.